Pyrrolidine Based Trifluro Organocatalyst: A Trap for syn Isomer of Functionalized Piperidines - B. Thorat, Prashant; V. Goswami, Santosh; V. Lokhande, Manohar; R Bhusare, Sudhakar (Current Organocatalysis, 2015)
The pyrrolidine trifluoro based organocatalyst has been found to be an efficient catalyst for the synthesis of syn and anti isomer of highly substituted piperidines. The trifluorine is used to trap syn isomer of functionalized piperidines. The one-pot synthesis via multi-component reaction of methylacetoacetate, aromatic aldehydes and various amines in ethanol at 80°C condition to afford pure anti product in excellent yield and pure syn isomer at lower temperature in some cases with moderate yield of products. At room temperature the product was obtained as syn:anti mixture with anti isomer as dominant in almost all cases.
Keywords: functionalized piperidine